A Critical–Collaborative Learning Model for Fostering Creative Thinking and Collaboration in Physics Teacher Education - Irwandani, Irwandani; Suyatna, Agus; Haenilah, Een Yayah; Maulina, Dina (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2026)
Preparing future physics teachers requires instructional models that intentionally integrate critical pedagogy, collaborative learning, and socioscientific inquiry to cultivate essential twenty-first-century competencies. However, existing approaches rarely connect these dimensions within a coherent instructional framework. This study developed and evaluated the Critical–Collaborative Learning Model (CCLM) to foster creative thinking and collaboration among prospective physics teachers. A research and development approach adapted from the Borg and Gall model was implemented through needs analysis, model design, expert validation, formative evaluation, and field testing. Data were collected using validation sheets, practicality questionnaires, creative-thinking assessments, and collaboration-skill questionnaires. The findings indicate that CCLM demonstrated high validity and practicality and produced stronger creative thinking and collaboration outcomes than conventional instruction. The model encouraged critical literacy, collaborative dialogue, creative production, and action-oriented learning through engagement with socioscientific issues, enabling students to generate more original ideas while strengthening collaborative problem-solving and shared responsibility. This study contributes a validated instructional framework that systematically integrates critical pedagogy and collaborative inquiry to support the development of higher-order competencies in physics teacher education.